Potential value of cerebrospinal fluid α-synuclein in the identification of postoperative delirium undergoing knee/hip arthroplasty: The perioperative neurocognitive disorder and biomarker lifestyle study - Lin, Xu; Guo, Yuwei; Dong, Rui; Wang, Bin; Bi, Yanlin (Frontiers in Neuroscience, 2022)
Objective: Postoperative delirium (POD) is a common postoperative complication, which may be associated with α-synuclein (α-syn). The purpose of this study was to explore the association between the expression level of α-syn in cerebrospinal fluid (CSF) and POD. Methods: We conducted a prospective observational cohort study, which were involved in 740 participants (mean age of 61.86 years, range 40 to 90 years; 40% female) from the Perioperative Neurocognitive Disorder And Biomarker Lifestyle (PNDABLE) study in the final analysis. POD was diagnosed using the Confusion Assessment Scale (CAM), and its severity was measured using the Memorial Delirium Assessment Scale (MDAS). Enzyme-linked immune-sorbent assay (ELISA) was used to detect the concentrations of α-syn, Aβ40, Aβ42, T-tau, and P-tau in CSF. Results: The incidence of POD was 11.22% (83/740). The logistic regression analysis showed that the increased concentrations of CSF α-syn (OR=1.005, 95%CI 1.004-1.006, P<0.001), P-tau (OR=1.093, 95%CI 1.071-1.115, P<0.001) and T-tau (OR=1.008, 95%CI 1.006-1.009, P<0.001) were risk factors of POD. Linear regression showed that CSF α-syn had positive correlations with P-tau (β=0.480, P<0.001), T-tau (β=0.334, P<0.001), while negative correlations with Aβ40 (β=-0.378 P<0.001), Aβ42 (β=-0.800, P=0.001) in POD patients. Mediation analyses showed the association between α-syn and POD was partially mediated by tau pathologies (proportion:16% to 17%). Conclusion: CSF α-syn is one of the preoperative risk factors for POD, which may be mediated through tau pathologies.